2015
DOI: 10.1093/mnras/stu2704
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of embedded planets’ first atmospheres – II. A rapid recycling of atmospheric gas

Abstract: Following Paper I we investigate the properties of atmospheres that form around small protoplanets embedded in a protoplanetary disc by conducting hydrodynamical simulations. These are now extended to three dimensions, employing a spherical grid centred on the planet. Compression of gas is shown to reduce rotational motions. Contrasting the 2D case, no clear boundary demarcates bound atmospheric gas from disc material; instead, we find an open system where gas enters the Bondi sphere at high latitudes and leav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
214
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(236 citation statements)
references
References 42 publications
18
214
0
1
Order By: Relevance
“…With mesh refinement applied only to the vicinity of the core, it would be possible to more reliably determine the fate of more strongly coupled particles (for applications toward smaller disk radii, millimetercentimeter sized pebbles already become strongly coupled with τ s 0.01). In particular, in the vicinity of embedded planetary cores, complex 3D flow structures have been found on the scale of the core's Bondi radius (Ormel et al 2015;Fung et al 2015), which may affect the accretion of strongly coupled particles.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…With mesh refinement applied only to the vicinity of the core, it would be possible to more reliably determine the fate of more strongly coupled particles (for applications toward smaller disk radii, millimetercentimeter sized pebbles already become strongly coupled with τ s 0.01). In particular, in the vicinity of embedded planetary cores, complex 3D flow structures have been found on the scale of the core's Bondi radius (Ormel et al 2015;Fung et al 2015), which may affect the accretion of strongly coupled particles.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Such an onion-shell structure would have less H 2 dissolved in the magma, and (for a nebula volatile source) less H 2 O in the atmosphere, than for our default model. Finally, the magma ocean might form volatilepoor if silicate cores reach full size in an environment that has a low base-of-atmosphere pressure (e.g., Ormel et al 2015). In this last case, convection is needed for non-negligible equilibration (Pahlevan et al 2019).…”
Section: How Long For Magma-atmosphere Equilibration?mentioning
confidence: 99%
“…In this study, we assume that a disk gas freely flows into a planet until atmospheric contraction due to radiative cooling occurs. Recently, Ormel et al (2015) found that a rapid recycle of the atmospheric gas suppresses gas accretion onto a planet embedded in an isothermal disk, whereas Kurokawa & Tanigawa (2018) showed that the atmospheric recycling of a planet should be less efficient in non-isothermal cases because of the buoyancy barrier. In addition, small grains may be suspended in an accreting H 2 -rich gas flow, leading to the delay of atmospheric cooling (Lambrechts & Lega 2017).…”
Section: Gas Accretion Onto a Planetmentioning
confidence: 99%